A series of five population‐specific Indian brain templates and atlases spanning ages 6–60 years. Issue 18 (26th August 2020) - Holla, Bharath; Taylor, Paul A.; Glen, Daniel R.; Lee, John A.; Vaidya, Nilakshi; Mehta, Urvakhsh Meherwan; Venkatasubramanian, Ganesan; Pal, Pramod Kumar; Saini, Jitender; Rao, Naren P.; Ahuja, Chirag K.; Kuriyan, Rebecca; et al.
Abstract: Anatomical brain templates are commonly used as references in neurological MRI studies, for bringing data into a common space for group‐level statistics and coordinate reporting. Given the inherent variability in brain morphology across age and geography, it is important to have templates that are as representative as possible for both age and population. A representative‐template increases the accuracy of alignment, decreases distortions as well as potential biases in final coordinate reports. In this study, we developed and validated a new set of T1w Indian brain templates (IBT) from a large number of brain scans (total n = 466) acquired across different locations and multiple 3T MRI scanners in India. A new tool in AFNI, make_template_dask.py, was created to efficiently make five age‐specific IBTs (ages 6–60 years) as well as maximum probability map (MPM) atlases for each template; for each age‐group's template–atlas pair, there is both a "population‐average" and a "typical" version. Validation experiments on an independent Indian structural and functional‐MRI dataset show the appropriateness of IBTs for spatial normalization of Indian brains. The results indicate significant structural differences when comparing the IBTs and MNI template, with these differences being maximal along the Anterior–Posterior and Inferior–Superior axes, but minimal Left–Right. For each age‐group, the MPM brain atlases provide reasonably good representation of the native‐space volumes in the IBT space, except in a few regions with high intersubject variability. These findings provide evidence to support the use of age and population‐specific templates in human brain mapping studies. Highlights: A new set of age‐specific T1w Indian brain templates for ages 6–60 yr are developed and validated. A new AFNI tool, make_template_dask.py, for the creation of group‐based templates. Maximum probability map atlases are also provided for each template. Results indicate the appropriateness of Indian templates for spatial normalization of Indian brains.